FACTORES ASOCIADOS AL ÉXITO DE LA NUTRICIÓN VIA ORAL PRECOZ EN PANCREATITIS AGUDA - Castro Perez, Dante Isaac; Chirinos Alvarado, Juan Pablo; Roque Quezada, Juan Carlos Ezequiel (Revista de Cirugía, 2022)
Ver carta al editor